2014
DOI: 10.1182/blood-2014-03-562231
|View full text |Cite
|
Sign up to set email alerts
|

Increased T follicular helper cells and germinal center B cells are required for cGVHD and bronchiolitis obliterans

Abstract: Key Points• T follicular helper cells and germinal center B cells are increased and strongly correlate with the development of cGVHD in a murine model. • Blocking mAbs for IL-21, ICOS, and CD40L are potential novel therapeutics for cGVHD.Chronic graft-versus-host disease (cGVHD) is a leading cause of morbidity and mortality after allogeneic hematopoietic stem cell transplantation. Having shown that germinal center (GC) formation and immunoglobulin deposition are required for multiorgan system cGVHD and associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
218
1
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 186 publications
(242 citation statements)
references
References 35 publications
20
218
1
3
Order By: Relevance
“…[47][48][49][50] Elevated levels of IL-21 51 and IL-21-producing cells 52 have been found in human cGVHD and a deleterious role of IL-21 has been demonstrated in mouse models of cGVHD. 25,52 Accordingly, we found relatively high basal levels of phosphorylated STAT3 as well as increased circulating plasmablasts in cGVHD patients in our study.Breg frequencies were increased after ECP treatment in 5 patients. ECP possibly induces Tregs through incompletely elucidated For personal use only.…”
mentioning
confidence: 52%
See 2 more Smart Citations
“…[47][48][49][50] Elevated levels of IL-21 51 and IL-21-producing cells 52 have been found in human cGVHD and a deleterious role of IL-21 has been demonstrated in mouse models of cGVHD. 25,52 Accordingly, we found relatively high basal levels of phosphorylated STAT3 as well as increased circulating plasmablasts in cGVHD patients in our study.Breg frequencies were increased after ECP treatment in 5 patients. ECP possibly induces Tregs through incompletely elucidated For personal use only.…”
mentioning
confidence: 52%
“…GC reactions are hardly accessible for studies in humans, but have indeed been shown to play a role in mouse models of cGVHD. 25,26 Further mechanistic studies will define the accurate role of the different B cells subsets in regulating the alloimmune response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We demonstrated recently that, consistent with this, systemic IL-17 levels increase late after clinical BMT, at a time when cGVHD develops (45). It is also clear that T follicular helper (T FH ) cells and IL-21 play important roles in the development of cGVHD via the stimulation of germinal center B cells and alloantibody generation (46). This is particularly relevant to bronchiolitis obliterans, because preliminary evidence suggests that Th17 differentiation and CSF1 dysregulation are also involved in this aberrant immunological pathway (44).…”
Section: Cytokines and Cgvhdmentioning
confidence: 64%
“…Homozygosity at the MHC in inbred mice allows for controlled analysis of the effect of the degree of major and minor antigen mismatch between donor and recipient on the outcome of GVHD severity and target organ pathogenesis. Depending on the donor and recipient mice strains and the degree of disparity at the MHC, major and minor mismatch may result in either acute [21,22] or chronic GVHD [23,24]. Further, the type of GVHD that manifests may be either CD4+ or CD8+ T cellmediated, depending on the murine model used and the differential reconstitution of T-cell subsets after HSCT.…”
Section: Differences In Agvhd Responses Between Speciesmentioning
confidence: 99%